(untitled) (Current Horticulture, 2024)
The effect of pre-harvest application of growth regulators on yield and quality of elephant-foot yam (Amorphophallus paeoniifolius Dennst.) was studied during storage at Horticultural College and Research Institute, TNAU, Coimbator,e during 2017-18. Thirteen pre-harvest treatments with cycocel, ethrel and kinetin were used individually and in combination with ridomil at different concentrations 15 days and 30 days before harvesting. The combination of cycocel @ 500 ppm + ridomil @ 0.5% sprayed 30 days before harvesting recorded highest mean corm weight (820.60 g) and yield 36.70 tonnes/ha. After harvesting, corms were stored in well-ventilated dry room with relative humidity of 60-75 %. There was a significant loss in corm weight, starch content, dry matter and oxalate content during storage. The corm weight was significantly higher in T8 (791.60 g), followed by T11 (773.30 g) and T2 (686.10 g) after 6 months of storage. There was no significant loss in starch and dry-matter content in corms in all treatments during storage. The starch content ranged from 8.96 to 10.20% and dry-matter content from 21.50 to 25.25%. The oxalate content was significantly lower in T8 (115.5 mg/100g), followed by T2 (120 mg/100g) and T9 (123 mg/100g).